Preliminary findings for preemptive analgesia with inhaled morphine - Onal, Selami Ates; Keles, Erol; Toprak, Gonca Caglar; Demirel, Ismail; Alpay, H. Cengiz; Avci, Levent (Mosby, Inc, 2006)
OBJECTIVE: The aim of this study was to assess file efficacy of inhaled morphine for preemptive analgesia in patients who undergo septoplasty or septorhinoplasty. STUDY PLAN AND METHODS: Eighty ASA I-II patients scheduled for septoplasty or septorhinoplasty were recruited and randomly divided into 2 groups that received different treatments 10 minutes prior to induction. The preemptive analgesia group (Group P, n = 40) received 65 mu g kg(-1) morphine sulphate (a 3-mL Volume) via an oral nebulizer, and the control group (Group C. n = 40) received 3 mL 0.9% sodium chloride (physiological saline) via the same type of nebulizer. Blood pressure, oxygen saturation, heart rate, time to first requirement for analgesia. and occurrence of nausea/vomiting were recorded. RESULTS: There were no significant differences between Groups P and C with respect to age, body weight. sex distribution. or duration Of surgery. There was also no significant difference between the group frequencies of postoperative nausea/vomiting. The time to first requirement for analgesia was significantly longer in Group P than Group C. CONCLUSION: The results of this preliminary study suggest that a single dose of inhaled morphine administered preemptively prior to septoplasty or septorhinoplasty provides effective postoperative analgesia.
Keywords: Postoperative Pain; Nebulized Morphine; Fentanyl; Surgery; Opioids; Ketamine